Late Neolithic and Early Bronze Age settlements and agro-pastoral developments in the Oslo Fjord area, southeastern Norway - Sand-Eriksen, Anette; Mjærum, Axel (Danish Journal of Archaeology, 2023)
The transition to the Late Neolithic (c. 2350 BCE) is characterised by large-scale cultural and economic changes across southern Norway, connected to the spread of a cultural package with an unprecedented homogeneity, consisting of the introduction of the two-aisled houses, farming and several new technologies. Although material components belonging to this cultural package spread fast in southern Norway, the Oslo Fjord area included, there has been a lack of (two-aisled) houses and clear evidence of the breakthrough of farming in this area. In this article, we aim to create a proxy for better understanding the agricultural developments and the trajectories of the early farm-based settlements in the aftermath of the LN revolution. This is done through studying the settlement material from three selected case areas around the Oslo Fjord, alongside a larger body of radiocarbon-dated buildings, cereals and cultivation layers. Our results show a delay in the onset of crop farming compared to the establishment houses in the region, which also contrasts the more abrupt changes in the material culture around 2350 BCE. This demonstrate the likelihood of a more gradual and adaptive farming development in this particular area of southern Norway.